Prose Pelaksanaan Rekrutmen Calon Pegawai Negeri Sipil Tahun 2010 (Studi Kasus Pada Badan Kepegawaian Daerah Kabupaten Sidoarjo) - Paskarina, Sarah (Jurnal Administrasi Publik, 2013)
Abstract: Prosess recruiting government employee candidates (a Case Study in the Local Employment  Agency of Sidoarjo Regency). The research methodology of this thesis include the type of research, the focus of research, types of data sources, data collection techniques, research instruments and data analysis. The results of this study are capable of independent Sidoarjo regency government in the implementation of recruitment of personnel resources. Implementation of the recruitment process includes the analysis of both employee needs analysis workload and job title. After that, make an announcement recruiting good candidates for Civil Servants in the mass media and electronic media, as well as the application, selection, admission and placement. Although there are still obstacles, among other constraints that occur in the process of implementation of the Civil Service recruitment candidates, such as technical errors made ​​by the applicants themselves. Constraints that occur in the implementation of recruitment of candidates for Civil Servants is able to be overcome by the committee organizers. Despite the obstacles that still occur in the recruitment process can be said to be exercising overall running as expected. Keywords: Recruitment, Government Employee Candidates Abstrak: Proses Pelaksanaan Rekrutmen Calon Pegawai Negeri Sipil Tahun 2010 (Studi Kasus Pada Badan Kepegawaian Daerah Kabupaten Sidoarjo). Metodologi penelitian skripsi ini meliputi jenis penelitian, fokus penelitian, jenis sumber data, teknik pengumpulan data, instrumen penelitian dan analisis data. Hasil Penelitian inilah adalah Pemerintah Kabupaten Sidoarjo mampu mandiri dalam pelaksanaan rekrutmen sumber daya aparatur. Proses pelaksanaan rekrutmen meliputi analisa kebutuhan pegawai baik analisa beban kerja dan jabatan. Setelah itu, memberikan pengumuman rekrutmen Calon Pegawai Negeri Sipil baik di media masa maupun media elektronik, serta pendaftaran, seleksi, penerimaan dan penempatan. Walaupun masih ada kendala, antara lain kendala yang yang terjadi dalam proses pelaksanaan rekrutmen Calon Pegawai Negeri Sipil ini, seperti kesalahan teknis yang dilakukan oleh calon pelamar itu sendiri. Kendala-kendala yang terjadi dalam pelaksanaan rekrutmen Calon Pegawai Negeri Sipil ini mampu diatasi oleh pihak panita penyelenggara. Meskipun kendala-kendala itu masih terjadi dalam proses pelakasanaan rekrutmen ini dapat dikatakan secara keseluruhan berjalan sesuai dengan yang diharapkan. Kata kunci : Rekrutmen, Calon Pegawai Negeri Sipil